Effects of task complexity and types of negotiation on language-related episodes in ESL classrooms - Ismail, Lilliati; Abd. Samad, Arshad (Infonomics Society, 2018)
While the use of pedagogical tasks to encourage learner-learner interaction has gained recognition in promoting interlanguage development, the ways in which language forms are dealt with during these interactions remain underexplored. This study addressed the noticing of gaps in language use while dealing with tasks which are reflected by the negotiation of meaning and negotiation of form that occurred. Employing classroom-based research, this study investigated the effects of task reasoning demand and type of negotiation on frequency of language-related episodes (LREs). The grammatical items that learners focused on during their interactions were also identified and tabulated. A repeated-measures design was adopted. The participants were 76 pre-university students randomly assigned into four groups. Data were analysed using descriptive statistics and repeatedmeasures ANOVA. Results indicate that there was a significantly higher number of LREs with negotiation of meaning as opposed to negotiation of form in the task with the high reasoning demand as opposed to the task with the low reasoning demand. The current research also shows that certain grammatical features were problematic for learners across both tasks. The results have implications on the utilization of tasks for L2 learning to optimize focus on meaning and form in learner-learner interaction.